Effect of an educational Program on Self-Care for Hypertensive Patients attending Soba University Hospital and Omdurman Military Hospital –Sudan - Dr. Hayat Fadlallah Mukhtar (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Hypertension is one of the most common chronic diseases and considered as a major risk factor for many medical conditions. The self-management is an effective approach for controlling of hypertension.Aim of study to assess the effectiveness of an educational program on self-management among hypertensivepatients.Methods: A quasi experimental research design one group was conducted in Soba University Hospital and Omdurman Military Hospital. Convenient sample  121 participants of adult hypertensive patients was selected. An educational program was intervened then all subjects followed up for six months. The pre and post data collected through the questionnaire and sphygmomanometer for measurement of blood pressure.  Result: There is significantly increase in compliance to antihypertensive drugs P value 0.006, adherence to lifestyle modifications significantly elevated  P value 0.003 , the basic knowledge of patients was significantly increased P value 0.003 , means of the baseline systolic and diastolic blood pressure were 148 mmHg and 93 mmHg where reduced to 144 mmHg and 89 mmHg at post-test respectively.Conclusion: The program significantly enhanced the patients to practice the self-care activities and led to reduction of the blood pressure.